Thymus ad astra, or spaceflight-induced thymic involution - Muramatsu, Wataru; Maryanovich, Maria; Akiyama, Taishin; Karagiannis, George S. (Frontiers in Immunology, 2025)
Spaceflight imposes a constellation of physiological challenges—cosmic radiation, microgravity, disrupted circadian rhythms, and psychosocial stress—that critically compromise astronaut health. Among the most vulnerable organs is the thymus, a cornerstone of immune system functionality, tasked with generating naive T cells essential for adaptive immunity. The thymus is particularly sensitive to spaceflight conditions, as its role in maintaining immune homeostasis is tightly regulated by a balance of systemic and local factors easily disrupted in space. Cosmic radiation, an omnipresent hazard beyond Earth’s magnetosphere, accelerates DNA damage and cellular senescence in thymic epithelial cells, impairing thymopoiesis and increasing the risk of immune dysregulation. Microgravity and circadian rhythm disruption exacerbate this by altering immune cell migration patterns and stromal support, critical for T-cell development. Psychosocial stressors, including prolonged isolation and mission-induced anxiety, further compound thymic atrophy by elevating systemic glucocorticoid levels. Ground-based analogs simulating cosmic radiation and microgravity have been instrumental in elucidating mechanisms of thymic involution and its downstream effects on immunity. These models reveal that long-duration missions result in diminished naive T-cell output, leaving astronauts vulnerable to infections and possibly at high risk for developing neoplasia. Advances in countermeasures, such as pharmacological interventions targeting thymic regeneration and bioengineering approaches to protect thymic architecture, are emerging as vital strategies to preserve immune resilience during prolonged space exploration. Focusing on the thymus as a central hub of immune vulnerability underscores its pivotal role in spaceflight-induced health risks. Understanding these dynamics will not only enhance the safety of human space missions but also provide critical insights into thymus biology under extreme conditions.